Effect of the non-uniform combustion core shape on the biochar production characteristics of the household biomass gasifier stove - Chaiyalap, Somchet; Chai-ngam, Ritthikrai; Saengprajak, Juthaporn; Piamdee, Jenjira; Putkham, Apipong; Saengprajak, Arnusorn (Center of Biomass & Renewable Energy (CBIORE), 2023)
The global demand for biochar in agricultural and carbon sequestration applications is increasing; nevertheless, biochar production using the 50-liter household biomass gasifier stove (50L-HBGS) in Thailand found major issues that need to be improved. The objective of this study was to study the effects of the airflow in the non-uniform combustion core shape (NCCS) on the biochar production characteristic of the 50L-HBGS. The new design of the NCCS was constructed and studied to replace the existing combustion core shape (ECCS) at Mahasarakham University. The height, air inlet, and air outlet diameters of the NCCS were designed at 45, 24, and 11.4 cm, respectively. The NCCS with 21 holes of the pyrolysis gas outlet, a diameter of 4 mm for each, was integrated into the 50L-HBGS and performed comparative tests to the ECCS using 9 kg of bamboo wood chunks in three consecutive experiments. The airflow and the combustion behavior were studied through the stove temperature profiles, which were recorded every 5 minutes using a digital data logger. The biochar products were studied using the scanning electron microscope (SEM) with the energy dispersive x-ray spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), and the proximate analysis technique. The study indicated that the 50L-HBGS with the NCCS made significantly improved the airflow rates in the combustion core, resulting in better continuous burning during the ignition state than with the ECCS. Moreover, the pyrolysis temperatures were significantly improved, it was provided temperatures during the pyrolysis process reached higher than 500 oC, resulting in the liquid tar being removed and no unburned wood chunks remaining at the end. The characterization result demonstrated that the 50L-HBGS with the NCCS had created biochar within a range of micropore and macrospore sizes and high fixed carbon content, which could be advantageously used for different agricultural and carbon sequestration applications.